The addition of strict stability criteria does not reduce recurrences after atrial fibrillation ablation using ablation index and can impact on procedure efficiency. (25th November 2020) - Parollo, M; Zucchelli, G; Guarracini, F; Marini, M; Di Cori, A; Barletta, V; De Lucia, R; Segreti, L; Bongiorni, M.G
Abstract: Background: Ablation Index (AI) is a proprietary lesion quality marker that combines power, contact force and time. Recent studies showed that radiofrequency (RF) pulmonary vein isolation (PVI) using AI can deliver high arrhythmia-free survival rates at mid-term follow-up in patients with paroxysmal atrial fibrillation. Purpose: The aim of this multicenter study was to compare the outcome of three different strategies of PVI using AI (group 1 and 2) or VISITAG module with average force and strict criteria of stability as target parameters (group 3). Methods: We enrolled 132 consecutive naive patients (97 males, mean age 61, 03±9, 42) affected by paroxysmal atrial fibrillation who underwent PVI at two high volume centres between January 2017 and February 2019. AI target was set at ≥380 at the posterior wall and ≥500 at the anterior wall. A strict stability criteria (VISITALY criteria: 3 mm for a time of 15 s and a FOT >5 g for 60% of the time) was set for Group 1 procedures (65 patients), whereas Group 2 procedures (67 patients) were carried out with standard stability criteria (VISTAX criteria: 3 mm for a time of 3 s and FOT >3 g for 25% of the time). We then compared those strategies with a historical cohort of 72 patients (40 males, mean age 60, 74±8, 53) treated at our centres with RF PVI using the VISITAG module with average force and strict stability criteria as target parameters. An interlesion distance ≤6 mm was a target parameter for all procedures. Recurrence was defined as any AF, atrial tachycardia (AT) or atrial flutter (AFL) during the 12 months after ablation, excluding a blanking period of 90 days. Results: There were no significant differences in terms of age (Group 1 59, 2±8, 97; Group 2 62, 81±9, 58; Group 3 60, 74±8, 53 years) and left atrial area (Group 1 24, 16±20, 46; Group 2 22, 55±12, 32; Group 3 20, 74±3, 84 cm 2 ). Group 1 showed a slightly higher number of males (Group 1 78, 46%; Group 2 68, 66%; Group 3 55, 56%; p=0, 004). Procedure duration was significantly lower in Group 2 compared to Groups 1 and 3 (176, 67±50, 88 vs 224, 05±47, 21 min, p<0, 001; 176, 67±50, 88 vs 203, 96±52, 38 min p=0, 02). Fluoroscopy time was significantly higher in Group 1 compared with Group 2 (11, 85±4, 38 vs 10, 39±6, 4 min; p=0, 014). There was a slight trend to have a higher freedom from AF/AT/AFL at 12 months in group 2 compared to the others (Group 1 86, 15% vs Group 2 91, 04% vs Group 3 84, 72%; p=0, 2). Conclusion: A strategy of PVI using AI with standard stability criteria performed the best in terms of procedure efficiency, with a significant benefit in terms of procedure duration, delivering a 12 months arrhythmia-free survival rate comparable with other strategies. Combination of AI with strict stability criteria provided no benefit, at a cost of a higher fluoroscopy time and longer procedure duration. Funding Acknowledgement: Type of funding source: None